Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/evj.12522
|View full text |Cite
|
Sign up to set email alerts
|

Preference for shelter and additional heat in horses exposed to Nordic winter conditions

Abstract: Horses selected shelters the most on days with precipitation and horses changed from a nonheated compartment to a heated compartment as weather changed from calm and dry to wet and windy. Horse breed category affected the use of shelter and body condition score and hair coat weight were associated with voluntary shelter selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Mental health issues can be a taboo subject within Traveller culture, with Traveller men in particular reluctant to discuss these issues [44], therefore, the subject of mental health and horse ownership within this group requires further investigation. Further, horses are often regarded as friends by Travellers rather than as possessions [89].…”
Section: Discussionmentioning
confidence: 99%
“…Mental health issues can be a taboo subject within Traveller culture, with Traveller men in particular reluctant to discuss these issues [44], therefore, the subject of mental health and horse ownership within this group requires further investigation. Further, horses are often regarded as friends by Travellers rather than as possessions [89].…”
Section: Discussionmentioning
confidence: 99%
“…Standardbred weanlings hence had equal opportunities as the Finnhorse weanlings to access the concentrate feed and the haylage. Jørgensen et al [ 51 ] reported that the adult Warmblood horses chose heated shelter more often than the Coldblood horses when weather was rainy and windy [ 51 ]. Since haylage was only available outside the shelter, it is possible that the Standardbred weanlings might have spent more time in the shelter and therefore ate less than their Finnhorse counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Morgan (1997 b) found that a dry winter coat had a thermal insulance of 0.123 m2 K W-1 in a cold and calm environment. Horses with a thick hair coat have been observed to spend more time outdoors during winter, compared to horses with a thinner hair coat (Jørgensen et al, 2016). This insulance might however vary considerably with differences in the hair coat characteristics.…”
Section: Hair Coat Characteristicsmentioning
confidence: 99%